Defining the “good” consultation: what is it and how could we measure it? - Corah, Louise V. (2019)
The consultation is an important and ubiquitous interaction in veterinary practice although the definition of a ‘good’ small animal veterinary consultation has yet to be identified. Using a mixed methods approach, this PhD thesis aimed to define what constitutes a good small animal veterinary consultation, identify important constituents, and ascertain which of these could be measured.